Measuring Human Capital in Small and Medium Manufacturing Enterprises: What Matters? - Mubarik, Muhammad Shujaat; Chandran, V.G.R.; Devadason, Evelyn Shyamala (Springer Verlag, 2018)
This study proposes a framework that quantifies and integrates both the tangible and intangible aspects of HC to comprehensively measure the overall level of human capital index (HCI) in small and medium manufacturing enterprises (SMEs). Data were collected from 100 SME experts through the use of questionnaires in two stages. The data collected were first, used for selection purpose, and second, for the prioritization of relevant dimensions and sub-dimensions of HC. The analytic hierarchy process was adopted to prioritize and assign dimension and sub-dimension weights to HC to derive the HCI. The results indicate that not all dimensions and sub-dimensions of HC are important for the HCI. Namely, the HCI can be best represented by 9 dimensions and 35 sub-dimensions of HC. The core dimensions are experience, skills, education, abilities and training. Indeed, within experience, the main sub-dimensions are work-related experience and organizational tenure. The results suggest the importance of experience relative to skills and education. The proposed framework can also be applied to derive industry specific HCI.